Hepatitis C Virus infection in Colombian populations with transfusion history and/or Population > 50 years old (2022)
ABSTRACT: MontoyaMelissa_2023_Hepatitis_B_Virus The active cases finding is a global priority taking into account the risk of end-stage liver disease associated with chronic Hepatitis C and the evidence of viral clearance and sustained virologic response in > 93% of patients with chronic HCV infection using Direct Action Antivirals (DAA) treatment in several studies. Moreover, the active case finding is one of the strategies of the World Health Organization plan for viral hepatitis control and elimination by 2030. In Colombian, 325.600 cases of HCV infection are estimated in general population based on the data of the Center for Disease Analysis (CDA). Interestingly, blood transfusion was the most frequent risk factor among the cohort of patients undergoing treatment through the centralized purchase of the Colombian Ministry of Health and Social Protection in 2019. In addition, history of injections using reused needles and syringes in health centers and pharmacies before the 90´s has been identified as a risk factor in the ”baby boomers” generation. Therefore, individuals with blood transfusion events before 1996 and people >50 years old are two important key populations for HCV infection in Colombia.